THE DIFFICULTIES OF STAFF WELFARE IN THE ORGANIZATION OF NIGERIAN PRISONSERVICE (NPS) AN INVESTIGATION OF OKE KURA PRISON, KWARA STATE NIGERIA - Kehinde Adekunle Aliyu; Jamaludin Mustaffa; Norruzeyati Binti Che Mohd Nasir (Proceedings of The ICECRS, 2016)
This paper looks at the "Nigerian Prison Service (NPS) and the difficulties of staff welfare organization: An investigation of Oke Kura prison, went for determining the degree to which welfare administrations were being managed in Oke Kura prison and the elements influencing it. Overview outline through organized poll was utilized to remove applicable information for the study. Speculation was tried utilizing chi-square (X2) measurable device. The study found that Oke Kura prison has been not able meet least U.N standard in welfare administrations on account of blockage. There is a constant utilization of pail lavatories which open inmates to wellbeing dangers. Aside from lacking assets, it was found that bungle of welfare assets has presented detainees to unfortunate circumstance, which can result to scourges and less than ideal passing of the inmates. We in this manner prescribed that administration ought to assemble more structures in the prison to oblige the perpetually expanding number of detainees, states governments ought to be permitted to make state confinement focuses as other option to penitentiaries, consistent preparing and retraining of prison staff in accordance with current worldwide best practices for prisons gets to be essential.